Ln(iv) complex, and a synthesis method and application thereof

By employing an electrochemical synthesis method with the synergistic effect of electron transfer media and solvents, the high cost and low yield problems in the synthesis of Tb(IV) and Pr(IV) complexes have been solved, achieving efficient and stable preparation of complexes, improving product purity and structural diversity, and promoting the development of functional materials.

CN122105426APending Publication Date: 2026-05-29SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610136842.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-01-30
Publication Date
2026-05-29

AI Technical Summary

Technical Problem

In the existing technology, the synthesis of Tb(IV) and Pr(IV) complexes faces problems such as high cost, low yield, instability and low product purity. Traditional methods are difficult to achieve efficient and stable preparation of high-valent lanthanide complexes.

Method used

An electrochemical synthesis method was adopted to electrolyze and oxidize the Ln(III) precursor in a mixed system of electron transfer medium, supporting electrolyte and solvent. Free radical cations were generated in situ on the electrode surface using electron transfer mediums such as thiaanthracene to realize the conversion of Ln(III) to Ln(IV). Stable Ln(IV) complexes were formed through the synergistic effect of acetonitrile solvent and auxiliary ligand.

Benefits of technology

It increased the synthesis yield to 90%, reduced reagent costs, enhanced product purity and single crystal preparation success rate, expanded the applicable range of ligands, increased the structural diversity of coordination compounds, and provided more options for the development of functional materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122105426A_ABST
    Figure CN122105426A_ABST
Patent Text Reader

Abstract

The application discloses an Ln(IV) complex and a synthesis method and application thereof, and belongs to the technical field of chemical synthesis. The synthesis method provided by the application comprises the following steps: electrolytic oxidation of an Ln(III) precursor in a mixed system of an electron transfer medium, a supporting electrolyte and a solvent; the electron transfer medium comprises at least one of thianthrene, tris(4-bromophenyl)amine, phenoxathiin and 10-methylphenothiazine; the supporting electrolyte comprises at least one of tetrabutylammonium tetrafluoroborate and tetrabutylammonium hexafluorophosphate; the solvent comprises acetonitrile; and the Ln(III) precursor comprises at least one of Pr(III) and Tb(III). The synthesis method provided by the application has the advantages of controllable process, low cost, high efficiency, high product yield, high purity, simple purification and the like. The application further provides the Ln(IV) complex synthesized by the synthesis method and application thereof.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of chemical synthesis technology, and in particular to an Ln(IV) complex, its synthesis method, and its application. Background Technology

[0002] The oxidation state of metal ions is a core factor determining their electronic structure, physicochemical properties, and application scenarios. Metal complexes with unconventional oxidation states (not the most stable or most common valence states of elements) have unique electronic configurations, providing ideal models for exploring fundamental chemical questions such as the nature of metal-ligand bonding and electron transfer mechanisms. They also show irreplaceable potential in the development of functional materials such as molecular magnets, qubits, and high-efficiency catalysts. Therefore, they have become a research hotspot in coordination chemistry, materials science, and quantum information.

[0003] Among numerous metallic elements, the study of unconventional oxidation state complexes of rare earth elements (especially lanthanides Ln) is particularly crucial. Most lanthanides are stable at +3 oxidation state, while +2 oxidation state (such as Sm) is more stable. 2+ Eu 2+ Yb 2+ ) and +4 valence (e.g., Ce) 4+ Cerium (Ce) is a relatively common unconventional oxidation state. Through systematic research by groups such as Kagan and Evans, the synthesis and structural characterization of +2 valence complexes of all rare earth elements have been achieved. Some +2 valence rare earth complexes have been proven to serve as highly active selective catalysts or high-performance molecular-based magnetic materials. However, +4 valence lanthanide complexes (mainly terbium Tb) are still relatively rare. 4+ He praseodymium Pr 4 + Research on ) has lagged behind for a long time, while research on higher valence states (such as Pr) has been lacking. 5+ The lack of coordination compounds has only been experimentally verified in recent years, which has become a key bottleneck restricting the development of high-end rare earth functional materials.

[0004] From an application perspective, Pr 4+ and Tb 4+ The complexes possess unique advantages: both contain only one isotope, providing a pure nuclear spin environment, and their hyperfine coupling between nuclear and electron spin holds promise for developing high-performance molecular spin qubits; simultaneously, Pr 4+ / Pr 3+ 、Tb 4+ / Tb 3+ High redox potentials (3.2V and 3.1V, respectively) vs . NHE) gives it potential applications in electrocatalysis, oxidation reactions, and other fields. Therefore, realizing Pr 4+ and Tb 4+The efficient and stable synthesis of complexes is of great significance for promoting basic research in rare earth chemistry and the industrialization of functional materials.

[0005] The synthesis of Tb(IV) and Pr(IV) complexes faces severe thermodynamic and experimental challenges: on the one hand, Tb 4+ / Tb 3+ The standard reduction potential is as high as 3.1V. vs NHE, Pr 4+ / Pr 3+ The reduction potential is 3.2V. vs The extremely high oxidation potential of NHE makes tetravalent ions readily reduced to trivalent ions, making them difficult to stabilize. On the other hand, the strong oxidizing properties of tetravalent lanthanides require ligands to possess oxidation resistance, strong coordination ability, and sufficient steric hindrance to prevent ligand oxidation or hydrolysis of the complex. Based on these requirements, currently only two types of ligands can stabilize Tb(IV) and Pr(IV): one is sterically hindered siloxy ligands, such as triphenylsiloxy and tri-tert-butylsiloxy, which hinder the reduction and hydrolysis of tetravalent ions through strong O→Ln coordination and large aryl / alkyl steric hindrance; the other is iminophosphine ligands, which use the lone pair electrons of the N atom to coordinate with the Ln atom. 4+ The formation of strong coordination bonds, along with the conjugated structure of the ligands dispersing the positive charge of the tetravalent ion, enhances the stability of the complex. Other types of ligands (such as carboxyl and alkoxy groups) are difficult to stabilize tetravalent lanthanides due to insufficient oxidation resistance or weak coordination ability, resulting in an extremely narrow range of ligand selection.

[0006] In traditional techniques, the synthesis of Tb(IV) and Pr(IV) complexes relies entirely on chemical oxidation, where the Ln(III) precursor is oxidized to Ln(IV) using a chemical oxidant, which then coordinates with a ligand to form a complex. The chemical oxidation process is carried out entirely in an argon glove box, where moisture causes hydrolysis of the precursor. The synthesis steps for the Pr(IV) precursor are as follows: Anhydrous PrCl3 (20 mmol, 5.31 g) is dispersed in 90 mL of tetrahydrofuran, and a tetrahydrofuran solution (1 M, 80 mL) of potassium bis(trimethylsilyl)amino (KN(SiMe3)2) is added. After stirring at room temperature for one week, the tetrahydrofuran is dried under vacuum. 100 mL of n-hexane is added to extract the product [KPr(N(SiMe3)2)4], and the insoluble matter is removed by filtration. The n-hexane solvent in the filtrate is removed under vacuum, and 20 mL of tetrahydrofuran is added to dissolve the product. Simultaneously, Ph3SiOH (8... 0 mmol (22.1 g) was dissolved in 20 mL of tetrahydrofuran; at room temperature, a tetrahydrofuran solution containing Ph3SiOH was slowly added to a tetrahydrofuran solution containing [KPr(N(SiMe3)2)4]; with vigorous stirring of the solution, the temperature of the reaction system gradually increased, indicating that it was an exothermic reaction; after the reaction was completed, 50 mL of n-hexane was added and mixed evenly with the solution. After a period of time, light green blocky crystals precipitated. After filtration, the crystals were washed with a mixed solution of tetrahydrofuran / n-hexane in a ratio of 1:4. The precipitate was collected, dried, and 14.9 g of product was obtained, with a yield of 49.8%. The synthesis of the Tb(IV) precursor includes the following steps: Anhydrous TbCl3 (20 mmol, 5.31 g) is dispersed in 90 mL of tetrahydrofuran, and a tetrahydrofuran solution (2 M, 30 mL) of sodium bis(trimethylsilyl)amino (NaN(SiMe3)2) is added. After stirring at room temperature for one week, the tetrahydrofuran is dried under vacuum. 100 mL of n-hexane is added to extract the product [Tb(N(SiMe3)2)3], and the insoluble matter is removed by filtration. The n-hexane solvent in the filtrate is removed under vacuum, and 20 mL of tetrahydrofuran solution is added. Solution: Simultaneously, Ph3SiOH (60 mmol, 16.6 g) was dissolved in 20 mL of tetrahydrofuran; at room temperature, the tetrahydrofuran solution containing Ph3SiOH was slowly added to the tetrahydrofuran solution containing [Tb(N(SiMe3)2)3]; with vigorous stirring of the solution, a white precipitate gradually precipitated, accompanied by a strong exothermic reaction; after filtration, the solution was washed with a mixed solution of tetrahydrofuran / n-hexane in a ratio of 1:4, and the collected precipitate was dried to finally obtain 14.4 g of product, with a yield of 60.0%.Taking Tb as an example, the oxidation and coordination steps are as follows: Tb(OSiPh3)3(THF)3 is dissolved in acetonitrile (MeCN), and an equal amount of oxidant (such as tris(4-bromophenyl)ammonium radical cation) is added. After stirring for two hours, a bright orange solid is separated by filtration. The main component of this orange solid is the Tb(IV) complex. Further crystallization in THF and toluene is carried out. At the same time, neutral chelating ligands (such as 2,2'-bipyridine, 1,10-phenanthroline, etc.) can be introduced to cultivate single crystals of the Tb(IV) complex. Taking Pr as an example, the oxidation and coordination process is as follows: Pr(IV) complex has good solubility in MeCN and will not precipitate directly as a solid. Neutral chelating ligands need to be introduced during the oxidation process to promote the precipitation of Pr(IV) complex. After filtration and separation, recrystallization with a toluene / n-hexane mixed solvent is required to obtain single crystals of the Pr(IV) complex.

[0007] The oxidation methods listed above have three major drawbacks. Firstly, the selection of oxidants is limited and significantly flawed: only a few oxidants (such as tris(4-bromophenyl)ammonium radical cations and thiamethoxammonium radical cations) can effectively oxidize Ln(III), and these oxidants are expensive (e.g., tris(4-bromophenyl)ammonium radical cations cost nearly 1000 yuan / 5 grams), have poor stability (easily affected by moisture or decompose), are dangerous to operate (requiring strict control of dosage under anhydrous and oxygen-free conditions), and even have high toxicity. Secondly, product separation and purification are difficult: the introduction of chemical oxidants easily generates byproducts (such as oxidant reduction products and ligand oxidation fragments), requiring purification through... The cumbersome separation and purification steps, such as column chromatography and multiple recrystallization, not only lead to a decrease in product yield (usually below 30%, for example, between 10% and 25%), but may also damage unstable Ln(IV) complexes during the purification process. Thirdly, the single crystal preparation has high uncertainty: the structural characterization of Ln(IV) complexes depends on X-ray single crystal diffraction, but the purity of products from chemical synthesis methods is uneven. Single crystal growth mostly needs to be obtained through methods such as freeze crystallization, liquid-phase diffusion crystallization, and gas diffusion crystallization, which rely on experience to optimize parameters such as temperature and solvent ratio, resulting in a low success rate (only about 50%). Some complexes cannot be structurally confirmed because single crystals cannot be obtained.

[0008] Besides the oxidation method mentioned above, electrochemical synthesis is also a commonly used method for synthesizing metal complexes, and has been used to prepare complexes of metals with conventional valence states (2 and +3) such as cobalt, tungsten, and ruthenium. However, its application in the preparation of unconventional oxidation state metal complexes has significant limitations. Traditional electrochemical synthesis techniques for metal complexes are briefly listed below: One is direct electrochemical synthesis, using a sacrificial metal anode as the core, such as copper anode dissolving in an acetonitrile system to generate Cu. + CN produced by the reduction of malononitrile cathode -The cyanocopper(I) complex was prepared by coordination with 2,2'-bipyridine (bpy), with a yield of 56.2%; or, organoruranecyclopentadienyl hydride complexes were synthesized via ECE process at 1.4V using a platinum cathode and a rhenium complex precursor, with a Faradaic efficiency of 96.8%; secondly, in-situ generation of organometallic-mediated organic synthesis was used, such as nickel-catalyzed electrochemical cross-coupling, using [NiBr2(bpy)] as a catalyst and sacrificial Mg / Zn anode as an electron source to achieve coupling of aryl halogens with pyridine derivatives; before the experiment, cyclic voltammetry was used to confirm the presence of Ni. 0 →Ni 2+ The oxidative addition mechanism was studied, and experimental conditions were then tailored accordingly. Furthermore, electrochemical synthesis methods can be used as supplementary research tools, such as cyclic voltammetry (CV) studies using a three-electrode system (platinum working electrode, Ag / Ag...). + The reference electrode is used to analyze the redox behavior of the complex, such as characterizing the redox peak of [NiBr(Mes)(bpy)], to guide the optimization of electrolysis parameters and improve synthesis efficiency and product purity.

[0009] In summary, the synthesis of unconventional oxidation state metal complexes such as Tb(IV) and Pr(IV) suffers from several drawbacks. Oxidation methods are costly, have limited raw material availability, poor safety, low yields, and difficulty in determining the crystal form of the products, hindering their functional expansion in fields such as magnetism and optics. Electrochemical methods are currently not feasible. Therefore, it is crucial to provide a low-cost, highly controllable, high-yield, and high-purity preparation method for unconventional oxidation state metal complexes. Summary of the Invention

[0010] This invention aims to solve at least one of the technical problems existing in the prior art. To this end, this invention proposes a method for synthesizing Ln(IV) complexes, which can effectively improve the synthesis yield and product purity of Ln(IV) complexes, and the synthesis process is direct, efficient, environmentally friendly, universally applicable, low-cost, and controllable.

[0011] The present invention also provides Ln(IV) complexes synthesized by the above-described synthetic method.

[0012] The present invention also provides applications of the above-mentioned Ln(IV) complex.

[0013] According to an embodiment of a first aspect of the present invention, a method for synthesizing an Ln(IV) complex is provided, the method comprising the following steps:

[0014] Electrolytic oxidation of Ln(III) precursor in a mixed system of electron transfer medium, supporting electrolyte and solvent; The electron transfer medium includes at least one of thiaanthracene (CAS: 92-85-3), tris(4-bromophenyl)amine (CAS: 4316-58-9), phenothiazine (CAS: 262-20-4), and 10-methylphenothiazine (CAS: 1207-72-3); The supporting electrolyte includes at least one of tetrabutylammonium tetrafluoroborate (CAS: 429-42-5) and tetrabutylammonium hexafluorophosphate (CAS: 3109-63-5); The solvent includes acetonitrile; The Ln(III) precursor includes at least one of Pr(III) and Tb(III).

[0015] The mechanism of the synthesis method is as follows: Anodic reaction (oxidation process): After energization, an oxidation reaction occurs on the electrode surface involving the electron transfer medium (taking thiaanthracene (Th) as an example): Th-e - →Th +. (Thiaanthracene radical cation, an electron transfer medium generated in situ); Th +. Electron transfer occurs with the Ln(III) precursor in the anode chamber: Ln(III) + Th +. →Ln(IV) + Th (Th is regenerated and enters the next catalytic cycle); Ln(IV) reacts with Ph3SiO in the solution. - Rapid coordination between the precursor or, if necessary, the main ligand and auxiliary ligands form the target complex Ln(OSiPh3)4L. x (Ln=Pr, Tb, L) x As the reaction proceeds (as an auxiliary ligand), some of the complexes, due to their low solubility, may deposit on the anode surface or precipitate at the bottom of the anode chamber. Cathodic reaction (reduction process): n-Bu4N in the cathode chamber + (Supporting electrolyte) gains electrons at the platinum cathode surface: n-Bu4N + +e - →n-Bu3N+C4H8 (Hofmann elimination reaction, producing tributylamine and 1-butene, some of the C4H8 is further hydrogenated to produce C4H 10 ); cathode byproducts (n-Bu3N, C4H8, C4H) 10 It is a gas or a liquid that is easily soluble in MeCN, does not react with the anode products, and some gaseous byproducts can be removed by argon purging; Ion migration: Ions in the electrolyte (supporting BF4 in the electrolyte) - Ph3SiO in Ln(III) precursor - Or support PF6 in the electrolyte -By migrating to the vicinity of the anode, the two chambers are kept electrically neutral, ensuring a continuous and stable current.

[0016] The control method according to embodiments of the present invention has at least the following beneficial effects: Electrochemical synthesis, as an environmentally friendly and controllable synthetic method, has the following advantages: the direction of redox reactions can be precisely controlled by adjusting the electrode potential, avoiding side reactions caused by chemical oxidants; the reaction system is closed, reducing environmental interference; and electrons are used as "clean reagents," producing no waste. However, traditional electrochemical synthesis relies on sacrificial anodes to provide metal ions and has not yet been applied to the synthesis of high-valence lanthanide complexes (such as Tb(IV) and Pr(IV)). The core reason is that Ln 4 + / Ln3 4+ High reducing potential (Tb) 4+ / Tb 3+ 3.1V vs NHE; Pr 4+ / Pr 3+ 3.2V vs The stability window of Ln(IV) exceeds that of conventional electrochemical systems. Direct anodic oxidation easily leads to solvent or ligand decomposition, making it impossible to synthesize Ln(IV) complexes. At the same time, there is a lack of mediator systems that can stabilize Ln(IV) and promote electron transfer in an electrochemical environment, resulting in extremely low oxidation efficiency. In addition, ionic liquids or supporting electrolytes in the electrolyte may undergo side reactions with Ln(IV) (such as coordination competition), and there is a lack of ligand systems that can stabilize Ln(IV), resulting in the inability to form the target complex. There is also a lack of mediator and ligand synergistic systems that can stabilize Ln(IV).

[0017] The electron transfer medium used in this invention can lose electrons to become a free radical that can oxidize Ln(III) to Ln(IV). After the experimental oxidation, it can return to its initial state and will not form a tight coordination with Ln(III) or Ln(IV). Due to the selection of a suitable electron transfer medium, the synthesis method provided by this invention, in addition to having the advantages of electrochemical synthesis in traditional technology, also introduces a commercially available electron transfer medium with a catalytic amount (significantly lower than stoichiometric) (such as thiazolium, which costs 1 / 50 of the oxidant used in traditional chemical oxidation methods). The free radical cations generated in situ on the electrode surface by the medium achieve the oxidation of Ln(III) → Ln(IV), avoiding the use of expensive and sensitive chemical oxidants with a stoichiometric amount. At the same time, electron transfer media such as thiazolium can be recycled (reduced to the initial state after oxidizing Ln(III)), which can reduce reagent costs while achieving Ln oxidation.

[0018] The solvent used in this invention includes acetonitrile, which has high solubility (>0.1 mol / L) for Ln(III) precursors, thiazolyl and other electron transfer media, and supporting electrolytes, but low solubility (<0.01 mol / L) for Ln(IV) complexes. This allows 18 of the 54 target complexes to be directly deposited in single-crystal form, meeting X-ray diffraction requirements, with only a few requiring simple recrystallization. This significantly improves the preparation efficiency and product purity of single-crystal Ln(IV) complexes. Complex purification steps such as column chromatography are eliminated, increasing product yield to as high as 90%. Furthermore, the choice of solvent also affects the space group of Ln(IV) complexes to some extent; selecting a suitable solvent can yield crystals with new space groups.

[0019] The synthesis method provided by this invention utilizes the precise temperature control (constant voltage / current) and reaction selectivity of electrochemical synthesis, reducing the formation of by-products and improving the purity of the obtained product.

[0020] An electrochemical synthesis method can be used, which can be combined with cyclic voltammetry to complete high-throughput screening of the synthesis system and find new synthesis systems for Tb(IV) and Pr(IV) complexes.

[0021] The synthesis method provided by this invention can improve the success rate of preparing single crystals of Ln(IV) complexes and help with structural characterization. By optimizing electrolysis parameters (such as voltage, supporting electrolyte type, and ligand concentration), most target complexes can be directly generated in the form of high-quality single crystals that meet the requirements of X-ray diffraction. Only a few complexes can be obtained as single crystals by simple recrystallization, which significantly reduces the uncertainty of single crystal preparation and provides a foundation for the study of the structure-property correlation of Ln(IV) complexes.

[0022] The synthesis method provided by this invention utilizes the synergistic effect of electrochemical synthesis, electron transfer media, and supporting electrolytes to expand the applicability of ligands (mainly auxiliary ligands) and enrich the structural diversity of coordination compounds by taking advantage of the mildness and selectivity of electrochemical oxidation. By introducing auxiliary ligands with different electronic effects and steric hindrance, a variety of new Pr(IV) and Tb(IV) coordination compounds are synthesized, expanding the existing tetravalent lanthanide coordination compound family by three times or more, and providing more structural options for the design and application of function-oriented Ln(IV) coordination compounds (such as single-molecule magnets and quantum bits).

[0023] The synthesis method provided by this invention establishes a universal electrochemical synthesis framework, expanding the ideas for the preparation of high-valence metal complexes. Using the electrochemical synthesis of Pr(IV) and Tb(IV) complexes as a model, the effectiveness of "electron transfer medium + mild electrolysis conditions" in the synthesis of high-valence metal complexes is verified. This provides a transferable technical solution for the preparation of other unconventional oxidation state metal complexes (such as Pr(V)), promoting the development of high-valence metal chemistry and materials science.

[0024] In summary, the synthesis method provided by this invention has significant advantages over traditional chemical oxidation synthesis methods in terms of synthesis efficiency, cost control, product quality, and versatility.

[0025] According to some embodiments of the present invention, the synthesis method further includes pretreatment equipment and reagents. The equipment pretreatment includes drying, and the reagent pretreatment includes molecular sieve dehydration or distillation dehydration. After pretreatment, the water content in the reagents used is <50 ppm.

[0026] According to some embodiments of the present invention, the electrochemical reaction apparatus for carrying out the synthesis method includes an anode chamber and a cathode chamber arranged with a sintered core; the Ln(III) precursor and electron transfer medium are disposed in the anode chamber; and the supporting electrolyte is disposed in the cathode chamber. The contents of the anode and cathode chambers are merely the initial placement positions of the raw materials. The presence of the sintered core reduces material exchange due to liquid flow, preventing large-scale mixing of the contents of the cathode and anode chambers, which could lead to a decrease in the yield of the Ln(IV) complex. However, in actual production, the raw materials will still slowly pass through the sintered core under diffusion; but the migration of the Ln(IV) complex is negligible, and the final product recovery is only performed on the contents of the anode chamber, thus reducing the amount of work done while having almost no impact on the product yield.

[0027] According to some embodiments of the present invention, the electrochemical reaction instrument is generally H-shaped, that is, the anode chamber and the cathode chamber are equivalent to the two vertical lines of the H-shape; the connection between the anode chamber and the cathode chamber is equivalent to the horizontal line of the H-shape, and the sand core is located in this horizontal line.

[0028] According to some embodiments of the present invention, the electrochemical reaction instrument is made of glass.

[0029] According to some embodiments of the present invention, the electrochemical reaction apparatus further includes an anode and a cathode; the anode is disposed in the anode chamber, and the cathode is disposed in the cathode chamber. The anode and cathode are made of platinum and are polished before use. This removes metal oxides or previously deposited Ln(IV) complexes from their surfaces.

[0030] According to some embodiments of the present invention, the sand core is a glass sand core.

[0031] The glass frit core has a pore size of 20-35 μm. This prevents the migration of Ln(IV) complexes (in the crystalline state) and their mixing with cathode byproducts, reducing the difficulty of subsequent product purification. It also allows the supporting electrolyte anions (or other anions) to migrate under the influence of the electric field to maintain electroneutrality, avoiding concentration polarization during electrolysis that could lead to reaction stagnation. In addition to charged supporting electrolyte ions, other raw materials can also be slowly exchanged between the anode and cathode chambers through diffusion in actual production. However, this diffusion exchange is very slow and still maintains the reaction environment in the anode chamber.

[0032] According to some embodiments of the present invention, the Ln(III) precursor includes at least one of KPr(OSiPh3)4(THF)3 and Tb(OSiPh3)3(THF)3.

[0033] In the Ln(III) precursor, the difference between the actual and theoretical contents of C, H, and Si elements is <0.3%; thus ensuring that the Ln(III) precursor has sufficient purity to meet the requirements for the preparation of high-purity Ln(IV) complexes.

[0034] According to some embodiments of the present invention, the mixed system further includes an auxiliary ligand, which includes at least one selected from N-heterocyclic chelating ligands, nitrile ligands, amide ligands, imidazole ligands, phosphine oxide ligands, sulfonyl ligands, and polyacid anions.

[0035] The π-electron system of the N-heterocyclic chelate ligand can interact with the 5d orbital of Ln(IV) (Ln=Pr, Tb) through π feedback, further dispersing the positive charge of Ln(IV) and reducing its oxidizing properties, thereby improving the stability of the Ln(IV) (Ln=Pr, Tb) complex.

[0036] The auxiliary ligands form chelate rings or solvate coordination with Ln(IV) through N / O atoms, further dispersing the positive charge of Ln(IV) and improving the stability of the resulting Ln(IV) complex. The synthesis method provided by this invention is compatible with a variety of auxiliary ligands, expands the diversity of complex structures, and solves the problem of narrow applicability of ligands in the prior art.

[0037] In actual production, the auxiliary ligand is located in the anode chamber.

[0038] According to some embodiments of the present invention, the nitrile ligand includes at least one of acetonitrile (CAS: 75-05-8), isobutyronitrile (CAS: 78-82-0; hereinafter referred to as L1) and 4-methoxybenzonitrile (CAS: 874-90-8; hereinafter referred to as L2).

[0039] According to some embodiments of the present invention, the N-heterocyclic chelating ligand includes 2,2'-bipyridine (CAS: 366-18-7; hereinafter referred to as L3), 4,4'-dimethyl-2,2'-bipyridine (CAS: 1134-35-6; hereinafter referred to as L4), 4,4'-dichloro-2,2'-bipyridine (CAS: 1762-41-0; hereinafter referred to as L5), 4,4'-dibromo-2,2'-bipyridine (CAS: 18511-71-2; hereinafter referred to as L6), 4,4'-dimethoxy-2,2'-bipyridine (CAS: 17217-57-1; hereinafter referred to as L7), 4,4'-di-tert-butyl-2,2'-bipyridine (CAS: 72914-19-3; hereinafter referred to as L8), and 4,4'-bis(trifluoromethyl)-2,2'-bipyridine. (CAS: 142946-79-0; hereinafter referred to as L9), methyl 2,2'-bipyridine-4,4'-dicarboxylate (CAS: 71071-46-0; hereinafter referred to as L10), 4,4'-dinitro-2,2'-bipyridine (CAS: 18511-72-3; hereinafter referred to as L11), 1,10-phenanthroline (CAS: 66-71-7; hereinafter referred to as L12), dipyrido[3,2-a:2',3'-c]phenazine (CAS: 19535-47-8; hereinafter referred to as L13), 1,10-o-diazaphenanthroline-5,6-dione (CAS: 27318-90-7; hereinafter referred to as L14), and at least one of 2-(quinolin-2-yl)-4,5-dihydrooxazole (CAS: 202191-12-6; hereinafter referred to as L15).

[0040] According to some embodiments of the present invention, the amide ligand includes at least one of N,N-dimethylformamide (CAS: 68-12-2; hereinafter referred to as DMF), N,N-diethylformamide (CAS: 617-84-5; hereinafter referred to as L16), N,N-diisopropylformamide (CAS: 2700-30-3; hereinafter referred to as L17), N-methylformanilide (CAS: 93-61-8; hereinafter referred to as L18), and N-methyl-N-(2-pyridyl)formamide (CAS: 67242-59-5; hereinafter referred to as L19).

[0041] According to some embodiments of the present invention, the imidazole ligand includes at least one of N-methylimidazolium (CAS: 616-47-7; hereinafter referred to as L20), 1-ethylimidazolium (CAS: 7098-07-9; hereinafter referred to as L21) and 1-propylimidazolium (CAS: 35203-44-2; hereinafter referred to as L22).

[0042] According to some embodiments of the present invention, the phosphine oxide ligand includes at least one of trimorpholinophosphine oxide (CAS: 4441-12-7; hereinafter referred to as L23) and di[2-[(oxo)diphenylphosphino]phenyl] ether (CAS: 808142-23-6; hereinafter referred to as L24).

[0043] According to some embodiments of the present invention, the sulfonyl ligand includes dimethyl sulfoxide (CAS: 67-68-5; hereinafter referred to as DMSO).

[0044] According to some embodiments of the present invention, the mixed system further includes a host ligand comprising a triphenylsiloxy group. The role of the host ligand is to compensate for the negative charge required for the oxidation of Ln(III) to Ln(IV), thereby maintaining charge balance; typically, Tb complexes require this, while Pr does not.

[0045] When synthesizing Tb complexes, the molar ratio of the host ligand to the Ln(III) precursor is 1:0.8 to 1.2; specifically, it can be 1:0.8, 1:1, 1:1.2, or any range of two of the above values. This is to compensate for the positive charge change from Tb(III) to Tb(IV).

[0046] Whether to add a main ligand is based on the composition of the Ln(III) precursor; in actual production, the triphenylsiloxy group (Ph3SiO2) needs to be controlled. - The molar ratio of triphenylsiloxy (Ph3SiO) to Ln(III) is 4:1 (designed molar ratio), of which triphenylsiloxy (Ph3SiO) - The sum of triphenylsiloxy groups in the Ln(III) precursor and the main ligand is required; if this condition is met, no additional main ligand is needed; otherwise, it is required.

[0047] The triphenylsiloxy (Ph3SiO) - It possesses a strong electron-donating ability (the lone pair electrons of the O atom form a coordinate bond with the 4f orbital of Ln(IV), and the triphenyl group has high steric hindrance, allowing it to encapsulate the Ln(IV) center; simultaneously, Ph3SiO - It has strong oxidation resistance and will not be oxidized by Ln(IV).

[0048] The dual-ligand system of the main ligand and the auxiliary ligand synergistically stabilizes Ln(IV), enabling it to form a stable complex.

[0049] In actual production, the main ligand is located in the cathode chamber.

[0050] According to some embodiments of the present invention, the host ligand includes KOSiPh3.

[0051] According to some embodiments of the present invention, the synthesis reaction is carried out in a water-proof environment. For example, in actual production, inert gases such as nitrogen or argon can be used for protection.

[0052] According to some embodiments of the present invention, the molar ratio of the electron transfer medium to the Ln(III) precursor is 0.002 to 1:1. Specifically, it can be 0.002:1, 0.005:1, 0.01:1, 0.015:1, 0.02:1, 0.03:1, 0.04:1, 0.05:1, 0.08:1, 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1.0:1; or a range of values ​​consisting of any two of the above points. Since the electron transfer medium is equivalent to a catalyst and can be recycled, the concentration of the electron transfer medium remains basically unchanged (error <5%) through cyclic voltammetry experiments, which means that almost 100% regeneration efficiency is achieved. It is also stable and will not undergo dimerization or decomposition reactions. Therefore, a small amount of electron transfer medium can be used to achieve continuous oxidation of Ln(III) precursor, reducing the reagent cost of electron transfer medium.

[0053] According to some embodiments of the present invention, the concentration of the supporting electrolyte in the cathode chamber is 0.06~0.13 mol / L. Specifically, it can be 0.06 mol / L, 0.08 mol / L, 0.1 mol / L, 0.12 mol / L, 0.13 mol / L; or a range of any two of the above values. This concentration refers to the initial concentration prepared at the beginning of the electrolytic oxidation. Subsequent discussions concerning the concentrations of the contents of the cathode and anode chambers will be explained similarly.

[0054] According to some embodiments of the present invention, the concentration of the Ln(III) precursor in the anode chamber is 8-12 mmol / L. For example, it can be 8 mmol / L, 9 mmol / L, 10 mmol / L, 11 mmol / L, 12 mmol / L; or a range of values ​​consisting of any two of the above points.

[0055] According to some embodiments of the present invention, in the mixed system, the molar ratio of the auxiliary ligand to the Ln(III) precursor is 1:0.8 to 1.2. For example, it can be 1:0.8, 1:1, 1:1.2; or a range of values ​​consisting of any two of the above points.

[0056] According to some embodiments of the present invention, in the mixed system, the molar ratio of the main ligand to the Ln(III) precursor is 1:0.8 to 1.2. For example, it can be 1:0.8, 1:1, 1:1.2; or a range of values ​​consisting of any two of the above points.

[0057] According to some embodiments of the present invention, the voltage of the electrolytic oxidation is higher than the oxidation potential of Ln(III) / Ln(IV). For example, When the Ln(III) precursor includes Tb(III), the electrolytic oxidation voltage can be selected from 4V to 6.5V, which is higher than the oxidation potential of Tb(III) / Tb(IV) 3.1V vs. NHE. For example, it can be 4.5V, 5V or 5.5V.

[0058] When the Ln(III) precursor includes Pr(III), the electrolytic oxidation voltage can be selected from 6V to 8.5V, which is higher than the oxidation potential of Pr(III) / Pr(IV) 3.2V vs. NHE. For example, it can be 6.5V, 7V, 7.5V or 8V.

[0059] At the same time, it is also necessary to select suitable electron transfer media and auxiliary ligands to avoid irreversible oxidation of electron transfer media and auxiliary ligands during electrolytic oxidation; thus, the synthesis method can be extended to the synthesis of other high-valence lanthanide complexes, breaking through the limitation of existing electrochemical methods that can only prepare low-valence metal complexes.

[0060] According to some embodiments of the present invention, the electrolytic oxidation temperature is room temperature. That is, without additional temperature control operations, comparable technical effects can be obtained within the range of 20~35°C.

[0061] According to some embodiments of the present invention, the duration of the electrolytic oxidation is 36 to 72 hours. Specifically, it can be 36 hours, 38 hours, 40 hours, 42 hours, 44 hours, 46 hours, 48 ​​hours, 50 hours, 52 hours, 54 hours, 56 hours, 58 hours, 60 hours, 65 hours, 70 hours, or 72 hours; or a range of values ​​consisting of any two of the above points.

[0062] According to some embodiments of the present invention, the synthesis method further includes purifying the product after the electrolytic oxidation.

[0063] For directly precipitated crystals, the purity is >98%, and no additional purification process is required.

[0064] For results where no crystals precipitate, the mixture in the anolyte needs to be concentrated until crystals precipitate. No further purification is required after concentration. The volume ratio of the concentrated crystals to the unconcentrated crystals is 1:15 to 25. Specifically, this could be 1:15, 1:20, 1:25, or any range of two of these values.

[0065] According to an embodiment of a second aspect of the present invention, an Ln(IV) complex is provided; the chemical formula of the Ln(IV) complex is Ln(OSiPh3)4L.x •aS; where Ln is Pr or Tb; x is any value between 0 and 2.5; a is any value between 0 and 3; L is the auxiliary ligand, and S is the solvent molecule. Specifically, x can be 0, 1, 2, or 2.5; a can be 0, 1, 2, 2.5, or 3. S can be acetonitrile or toluene.

[0066] The Ln(IV) complex provided in the second aspect of the present invention can be synthesized by the synthesis method provided in the first aspect of the present invention.

[0067] Furthermore, the Ln(IV) complexes provided by this invention either incorporate new auxiliary ligands or have new space groups; they are essentially different from Ln(IV) complexes synthesized by conventional techniques, and therefore are expected to achieve new technical effects in fields such as magnetism and optics.

[0068] According to some embodiments of the present invention, the chemical formula of the Ln(IV) complex is at least one of Ln(OSiPh3)4(MeCN)2, Ln(OSiPh3)4L•2MeCN, Ln(OSiPh3)4(L)2•2MeCN, Ln(OSiPh3)4L•MeCN, Ln(OSiPh3)4L, Ln(OSiPh3)4(L)2, Ln(OSiPh3)4(L)2•MeCN, Ln(OSiPh3)4L•(MeCN)(Tol)2 and Ln(OSiPh3)4L•3MeCN.

[0069] According to some embodiments of the present invention, the chemical formulas of the Ln(IV) complexes are Tb(OSiPh3)4(MeCN)2, Tb(OSiPh3)4(L1)2•MeCN, Pr(OSiPh3)4(L1)2•2MeCN, Tb(OSiPh3)4(L2)2•MeCN, Pr(OSiPh3)4(L2)2•2MeCN, Tb(OSiPh3)4L3•2MeCN, Pr(OSiPh3)4L3•2MeCN, Tb(OSiPh3)4L4•2MeCN, Pr(OSiPh3)4L4•2MeCN, Tb(OSiPh3)4L5•2MeCN, Pr ... )4L5·2MeCN, Tb(OSiPh3)4L6·2MeCN, Pr(OSiPh3)4L6·2MeCN, Pr(OSiPh3)4L7·MeCN, Tb(OSiPh3)4L7·2MeCN, Pr(OSiPh3)4L8·2MeCN, Tb(OSiPh3)4L8 •2MeCN, Tb(OSiPh3)4L9•2MeCN, Pr(OSiPh3)4L9•2MeCN, Tb(OSiPh3)4L10•2MeCN, Pr(OSiPh3)4L10•2MeCN, Tb(OSiPh3)4L11•MeCN, Pr(OSiPh3)4L11 •MeCN, Pr(OSiPh3)4L12•2MeCN, Tb(OSiPh3)4L12•2MeCN, Pr(OSiPh3)4L13•MeCN, Tb(OSiPh3)4L13•MeCN, Tb(OSiPh3)4L13•MeCN, Tb(OSiPh3)4L13, Tb(OSiPh3)4L13•(MeCN)(Tol)2, Pr(OSiPh3)4L14•MeCN, Tb(OSiPh3)4L14•MeCN, Pr(OSiPh3)4L15•3MeCN, Tb(OSiPh3)4L15•3MeCN, Pr(OSiPh3)4(D MF)2, Tb(OSiPh3)4(DMF)2, Tb(OSiPh3)4(L16)2, Pr(OSiPh3)4(L16)2, Tb(OSiPh3)4(L17)2•MeCN, Pr(OSiPh3)4(L17)2•MeCN, Tb(OSiPh3)4(L18)2• 2MeCN, Pr(OSiPh3)4(L18)2•2MeCN, Tb(OSiPh3)4(L19)2•2MeCN, Pr(OSiPh3)4(L19)2•2MeCN, Tb(OSiPh3)4(L20)2•MeCN, Pr(OSiPh3)4(L20)2•MeCN,Tb(OSiPh3)4(L21)2•MeCN, Pr(OSiPh3)4(L21)2•MeCN, Tb(OSiPh3)4(L22)2, Pr(OSiPh3)4(L22)2, Tb(OSiPh3)4L23•2MeCN , Pr(OSiPh3)4L23·2MeCN, Tb(OSiPh3)4L24·2MeCN, Pr(OSiPh3)4L24·2MeCN, Tb(OSiPh3)4(DMSO)2 and Pr(OSiPh3)4(DMSO)2. ,

[0070] According to some embodiments of the present invention, the space group of the Ln(IV) complex is R -3、 P -1、 P twenty one / n , P twenty one / c , C 2 / c , Pca 21 and Pccn One of them.

[0071] According to an embodiment of the third aspect of the present invention, an Ln(IV) complex synthesized by the synthesis method described in the first aspect of the present invention is provided, or the Ln(IV) complex as described in the second aspect of the present invention is used in the fields of coordination chemistry, catalysis, single-molecule magnets, magnetic semiconductors, low-temperature magnetocooling and quantum information.

[0072] Since the application employs all the technical solutions of the synthesis method or Ln(IV) complex of the above embodiments, it has at least all the beneficial effects brought about by the technical solutions of the above embodiments.

[0073] Other features and advantages of the invention will be set forth in the description which follows, and will be apparent in part from the description, or may be learned by practicing the invention. Attached Figure Description

[0074] The above and / or additional aspects and advantages of the present invention will become apparent and readily understood from the description of the embodiments taken in conjunction with the following drawings, in which: Figure 1 This is a schematic diagram of the electrochemical device used in the embodiments of the present invention.

[0075] Figure 2 The color changes during the synthesis process in the embodiments of the present invention are shown in (a) before the electrolysis reaction occurs; (b) during the electrolysis reaction; and (c) another situation after the electrolysis reaction is completed.

[0076] Figure 3This is the single crystal structure of the Tb(IV) complex obtained in Example 1 of this invention. In the figure, pink represents Tb atoms, red represents O atoms, blue represents N atoms, orange represents Si atoms, and gray represents C atoms; other atoms have been omitted.

[0077] Figure 4 This is the single crystal structure of the Ln(IV) complex obtained in Example 4 of the present invention. In the figure, pink represents Pr or Tb atoms, red represents O atoms, blue represents N atoms, orange represents Si atoms, and gray represents C atoms; other atoms have been omitted.

[0078] Figure 5 This is the single crystal structure of the Ln(IV) complex obtained in Example 5 of the present invention. In the figure, pink represents Pr or Tb atoms, red represents O atoms, blue represents N atoms, orange represents Si atoms, and gray represents C atoms; other atoms have been omitted.

[0079] Figure 6 This is the single crystal structure of the Ln(IV) complex obtained in Example 6 of the present invention. In the figure, pink represents Pr or Tb atoms, red represents O atoms, blue represents N atoms, orange represents Si atoms, green represents Cl atoms, and gray represents C atoms; other atoms have been omitted.

[0080] Figure 7 This is the single crystal structure of the Ln(IV) complex obtained in Example 7 of the present invention. In the figure, pink represents Pr or Tb atoms, red represents O atoms, blue represents N atoms, orange represents Si atoms, dark green represents Br atoms, and gray represents C atoms; other atoms have been omitted.

[0081] Figure 8 This is the single crystal structure of the Ln(IV) complex obtained in Example 8 of the present invention. In the figure, pink represents Pr or Tb atoms, red represents O atoms, blue represents N atoms, orange represents Si atoms, and gray represents C atoms; other atoms have been omitted.

[0082] Figure 9 This is the single crystal structure of the Tb(IV) complex obtained in Example 9 of the present invention. In the figure, pink represents Tb atoms, red represents O atoms, blue represents N atoms, orange represents Si atoms, and gray represents C atoms; other atoms have been omitted.

[0083] Figure 10 This is the single crystal structure of the Ln(IV) complex obtained in Example 13 of the present invention. In the figure, pink represents Pr or Tb atoms, red represents O atoms, blue represents N atoms, orange represents Si atoms, and gray represents C atoms; other atoms have been omitted.

[0084] Figure 11This is the single crystal structure of Tb(OSiPh3)4L13 obtained in Example 14 of the present invention. In the figure, pink represents Tb atoms, red represents O atoms, blue represents N atoms, orange represents Si atoms, and gray represents C atoms; other atoms have been omitted.

[0085] Figure 12 This is the single crystal structure of the Tb(IV) complex obtained in Example 16 of the present invention. In the figure, pink represents Tb atoms, red represents O atoms, blue represents N atoms, orange represents Si atoms, and gray represents C atoms; other atoms have been omitted.

[0086] Figure 13 This is the single crystal structure of the Ln(IV) complex obtained in Example 17 of the present invention. In the figure, pink represents Pr or Tb atoms, red represents O atoms, blue represents N atoms, orange represents Si atoms, and gray represents C atoms; other atoms have been omitted.

[0087] Figure 14 This is a schematic diagram of the mechanism of the synthesis method in the embodiments of the present invention.

[0088] Figure 15 The following are the structural formulas of the electron transfer media that can be selected in the embodiments of the present invention: (a) thiaanthracene; (b) phenoxathiazine; (c) 10-methylphenthiazine; (d) tris(4-bromophenyl)amine.

[0089] Figure 16 This is a graph showing the magnetic entropy change of the Tb(IV) complex obtained in Example 4 of the present invention. Detailed Implementation

[0090] The following will describe the concept and technical effects of the present invention clearly and completely with reference to embodiments, so as to fully understand the purpose, features and effects of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are all within the scope of protection of the present invention.

[0091] (1) The electrochemical device used in the specific implementation method is as follows: Figure 1 As shown. The electrochemical device includes a cathode chamber and an anode chamber, with a glass frit core positioned between them. The entire electrochemical device is made of glass, H-shaped, with the anode in the anode chamber and the cathode in the cathode chamber; both the anode and cathode are platinum electrodes. Its dimensions are 2cm × 2cm × 0.1mm. More specifically... Selection of glass frit: Use glass frit with a pore size of 20-35μm, which can prevent the Ln(IV) complex crystals of the anode from entering the cathode chamber, while allowing the free migration of anions in the electrolyte, thus maintaining the electroneutrality of both chambers.

[0092] Polishing treatment of platinum electrodes: Before each experiment, the surface of the platinum electrode is polished with 0.05μm alumina powder to remove residual metal oxides or Ln(IV) complex deposits, ensuring that the surface of the platinum electrode is fresh and dry, reducing the overpotential of the oxidation reaction and improving the electron transfer efficiency.

[0093] (2) The Ln(III) precursor used in the specific implementation method is synthesized in the manner described in reference DOI:10.1039 / D4SC08731C(2025), as shown in the background of this invention; the Ln(III) precursor used is KPr(OSiPh3)4 or Tb(OSiPh3)3. The purity was confirmed by elemental analysis (C, H, and Si element content error <0.3%).

[0094] (3) The specific implementation method uses KOSiPh3, which is synthesized entirely in a glove box. The specific steps are as follows: KH (10.1 mmol, 405 mg, 1.01 eq) is dispersed in 40 mL of tetrahydrofuran; at the same time, Ph3SiOH (10 mmol, 2.76 g, 1 eq) is dissolved in 100 mL of tetrahydrofuran; at room temperature, the tetrahydrofuran solution containing Ph3SiOH is slowly added to the KH suspension. As the solution is vigorously stirred, gas will be emitted from the reaction system; the reaction ends when no gas is emitted and the solution is relatively clear. The insoluble matter is removed by filtration, the tetrahydrofuran solvent in the filtrate is removed under vacuum, and the purity is confirmed by elemental analysis (C, H, and Si element content error <0.3%).

[0095] (4) The specific synthesis method used in the specific implementation is as follows. If there are any differences, they will be listed in the specific embodiments: S1. Preparation: Equipment pretreatment: Place the H-type electrolytic cell and other equipment in a 120℃ oven to dry for 12 hours, and after cooling, transfer them to an argon glove box for later use (to avoid residual moisture causing hydrolysis of the complex). Reagent pretreatment: Electron transfer medium and supporting electrolyte were vacuum dried at 60°C for 24 h to remove water of crystallization; all solvents were dried by molecular sieve (4 Å) and then further dehydrated by distillation (water content <50 ppm).

[0096] S2. To avoid cross-contamination, prepare separate electrolyte solutions for the anode chamber and the cathode chamber; the electrolyte solutions for the anode chamber and the cathode chamber are collectively referred to as the mixed system.

[0097] Preparation of electrolyte for the anode chamber: In an argon glove box, add the following reagents to the anode chamber: Ln(III) precursor: 0.20 mmol; thiahexane: 0.02 g (0.10 mmol, catalytic amount, molar ratio of 0.5 times that of Ln(III) precursor); auxiliary ligand (if present): 0.20 mmol (equal to the molar amount of Ln(III) precursor); dried MeCN: 20 mL; In actual production, depending on the types of reagents available, one can choose... Figure 15 Other reagents shown can be used to replace thiamethoxam to achieve similar technical results.

[0098] Cathode chamber electrolyte preparation: In an argon glove box, add the following reagents to the cathode chamber: Supporting electrolyte: approximately 0.10 mol / L; main ligand KOSiPh3 (if present): 0.20 mmol; dried MeCN: 20 mL.

[0099] S3. Electrolysis reaction (achieved in an argon atmosphere): Before energizing, the solutions in both the anode and cathode chambers are pale yellow or colorless, such as... Figure 2 As shown in Figure (a), after the DC power supply is turned on, the solution in the anode chamber quickly turns orange to red, as shown in Figure (a). Figure 2 As shown in Figure (b), the formation of Ln(IV) (Ln=Pr, Tb) complexes was observed. After two days of continuous electrolysis, red to dark red Ln(IV) (Ln=Pr, Tb) complex crystals appeared on the electrode surface and at the bottom of the electrolytic cell. Figure 2 As shown in Figure (c); in addition, due to the different raw materials, some of the electrolysis reaction does not crystallize, but remains a clear red to dark red solution (this part of the Ln(IV) (Ln=Pr, Tb) complex has high solubility in MeCN).

[0100] Parameter control during the electrolysis reaction process: Voltage settings: A constant voltage of 4V was applied when synthesizing the Tb(IV) complex, and a constant voltage of 6V was applied when synthesizing the Pr(IV) complex (determined by cyclic voltammetry experiments (CHI660E electrochemical workstation) to avoid slow reaction rate due to too low voltage and decomposition of MeCN due to too high voltage); Reaction time: 48h; Temperature control: room temperature (25℃), no heating or cooling required, to avoid temperature changes affecting the solubility and stability of the complex.

[0101] S4. Product separation and purification: Turn off the power and argon gas, disconnect the electrode connection, and open the feed port of the anode chamber.

[0102] The product is directly precipitated as a single crystal: red to dark red Ln(IV) (Ln=Pr, Tb) complex crystals appear on the electrode surface and at the bottom of the electrolytic cell by filtration and collection, and the target complex single crystal is obtained (purity >98%, which can be directly used for X-ray diffraction); the remaining red to dark red solution in the concentrated anode chamber can further precipitate Ln(IV) (Ln=Pr, Tb) complex; during the concentration process, the product precipitates, and the impurities remain in the concentrated crystallization mother liquor, so the precipitated crystals do not need further purification, and the purity and yield of the product can be guaranteed.

[0103] Highly soluble products: Transfer all the solution in the anode chamber to a rotary evaporator flask and concentrate it to 1 ml at 30 °C and 10 mmHg to obtain the corresponding Ln(IV) (Ln=Pr, Tb) complex.

[0104] Different products require different purification methods, which will be described in specific examples.

[0105] The reaction mechanism of the synthesis method is as follows Figure 14 As shown.

[0106] (5) The characterization methods of the products obtained by the specific implementation method are as follows: Single-crystal X-ray diffraction: The product single crystal was placed on a Bruker D8 VENTURE diffractometer, and diffraction data were collected at 100K using Mo-Kα radiation (λ=0.71073Å) as the light source. The structure was analyzed using Olex2 software combined with SHELXT / SHELXL program to confirm the coordination environment and valence state of the metal center of the complex. Elemental analysis: The content of C, H and N elements in the product was determined using a Carlo Erba EA1110 elemental analyzer and compared with the theoretical values ​​(error <0.3%) to verify the purity.

[0107] Example 1 In this example, Tb(IV) complexes and Pr(IV) complexes were prepared, respectively, wherein: (1) No additional auxiliary ligands and main ligands are added; the solvent acetonitrile acts as the auxiliary ligand.

[0108] (2) The supporting electrolyte is: tetrabutyltetrafluoroborate ammonium salt; (3) When synthesizing Tb(IV) complexes, the Ln(III) precursor is Tb(OSiPh3)3; and the main ligand KOSiPh3 is added at the same time. When synthesizing Pr(IV) complexes, the Ln(III) precursor is KPr(OSiPh3)4; and no main ligand is added.

[0109] (4) Synthesis of Tb(IV) complex, state of the anode chamber after electrolysis and Figure 2Similar to Figure (c), it contains both single crystals and a red to dark red solution; the solution in the anode chamber is concentrated to obtain the product, which is then combined with the single crystal; the overall yield is 65%. Synthesis of Pr(IV) complex, state of the anode chamber after electrolysis and Figure 2 Similar to Figure (b), it is a clear solution of red to dark red, with no single crystals precipitated; the solution in the anode chamber is concentrated to obtain the product, with a yield of 42%.

[0110] (5) Product characterization showed that the Tb(IV) complex was Tb(OSiPh3)4(MeCN)2, crystallized in the trigonal crystal system, with space group 4. R- 3. Single crystal structure, such as Figure 3 As shown, one asymmetric unit of this complex comprises a complete Tb(OSiPh3)4(MeCN)2 molecule and one-third highly disordered Tb(OSiPh3)4(MeCN)2 molecules. The Tb(IV) ions in both molecules are six-coordinated and located in a distorted octahedral coordination environment. The central Tb(IV) ion simultaneously interacts with four Ph3SiO4 molecules. - The anionic ligand is coordinated with two neutral acetonitrile ligands, and there are no additional equilibrium ions or free acetonitrile molecules, making the entire molecule neutral. The Tb(IV) ion interacts with Ph3SiO2. - The bond lengths between ligands, Tb-O, range from 2.015 to 2.089 Å, while the bond lengths between Tb(IV) ions and acetonitrile ligands, Tb-N, range from 2.462 to 2.565 Å. This molecule shares the same host structure as Tb(OSiPh3)4(MeCN)2 reported in the literature (Angew. Chem. Int. Ed. 59, 3549-3553, DOI: 10.1002 / anie.201914733(2020)), but due to different crystallization environments, their space groups and free solvents are different. Elemental analysis: C 76 H 66 N₂Si₄TbO₄: Calculated values: C, 67.98; H, 4.95; N, 2.09. Experimental values: C, 67.82; H, 5.01; N, 2.02. Here and in subsequent relevant locations, calculated and experimental values ​​are the mass percentages of the element.

[0111] Example 2 In this example, Tb(IV) complexes and Pr(IV) complexes were prepared respectively. The specific difference from Example 1 is as follows: (1) An auxiliary ligand, isobutyronitrile (L1), was added. (2) The state of the anode chamber after electrolysis during the synthesis of Tb(IV) complexes and Pr(IV) complexes. Figure 2Similar to Figure (b), there was no crystallization and a red to dark red solution; concentrating the solution in the anode chamber yielded an orange-red or red solid powder product; the chemical formulas of the Tb(IV) complex and the Pr(IV) complex were Tb(OSiPh3)4(L1)2•MeCN and Pr(OSiPh3)4(L1)2•2MeCN, respectively; the calculated yields were 46% Pr(IV) and 53% Tb(IV), respectively.

[0112] Elemental analysis C 82 H 77 N3Si4TbO4: Calculated values: C, 68.97; H, 5.51; N, 3.83. Experimental values: C, 68.88; H, 5.34; N, 3.80.

[0113] Elemental analysis C 84 H 80 N4Si4PrO4: Calculated values: C, 68.41; H, 5.39; N, 2.92. Experimental values: C, 68.37; H, 5.19; N, 2.99.

[0114] Example 3 In this example, Tb(IV) complexes and Pr(IV) complexes were prepared respectively. The specific difference from Example 1 is as follows: (1) An auxiliary ligand, 4-methoxybenzonitrile (L2), was added. (2) The state of the anode chamber after electrolysis during the synthesis of Tb(IV) complexes and Pr(IV) complexes. Figure 2 Similar to Figure (b), there was no crystallization and a red to dark red solution; the solution in the anode chamber was concentrated to obtain an orange-red or red solid powder product; the chemical formulas of the Tb(IV) complex and the Pr(IV) complex are Tb(OSiPh3)4(L2)2•MeCN and Pr(OSiPh3)4(L2)2•2MeCN, respectively; the calculated yields were 34% Pr(IV) and 51% Tb(IV), respectively.

[0115] Elemental analysis C 90 H 77 N3Si4TbO6: Calculated values: C, 68.97; H, 5.51; N, 3.83. Experimental values: C, 69.15; H, 5.60; N, 3.63.

[0116] Elemental analysis C 92 H 80N4Si4PrO6: Calculated values: C, 68.95; H, 4.95; N, 2.68. Experimental values: C, 69.08; H, 4.78; N, 2.78.

[0117] Example 4 In this example, Tb(IV) complexes and Pr(IV) complexes were prepared respectively. The specific difference from Example 1 is as follows: (1) An auxiliary ligand, 2,2'-bipyridine (L3), was added. (2) The state of the anode chamber after electrolysis during the synthesis of Tb(IV) complex Tb(OSiPh3)4L3•2MeCN and Pr(IV) complex Pr(OSiPh3)4L3•2MeCN. Figure 2 Similar to Figure (c), single crystals were precipitated and the solution was red to dark red. The solution in the anode chamber was concentrated to obtain an orange-red or red solid powder product. The concentrated product and the precipitated single crystals were combined, and the yields were calculated to be 63% Pr(IV) and 87% Tb(IV), respectively.

[0118] (3) Single crystal structures show that these two compounds are isomorphic, both crystallizing in the triclinic crystal system with space group 1. P -1, specifically as follows Figure 4 As shown. The central Ln(IV) (Ln=Pr, Tb) simultaneously reacts with four Ph3SiO4 atoms. - The anionic ligand coordinates with an L3 neutral ligand in a distorted octahedral coordination environment, resulting in a neutral molecule. Two acetonitrile molecules co-crystallize. Pr(IV) ions react with Ph3SiO - The bond lengths between ligands, Pr-O, range from 2.118 to 2.140 Å, while the bond lengths between Pr(IV) ions and L3 ligands, Pr-N, range from 2.564 to 2.574 Å. The bond lengths between Tb(IV) ions and Ph3SiO ions are also significant. - The bond lengths between ligands, Tb-O, range from 2.050 to 2.104 Å, and the bond lengths between Tb(IV) ions and L3 ligands, Tb-N, range from 2.465 to 2.472 Å.

[0119] Elemental analysis C 86 H 74 N4Si4TbO4: Calculated values: C, 69.46; H, 5.07; N, 3.52. Experimental values: C, 69.39; H, 4.88; N, 3.51.

[0120] Elemental analysis C 86 H 74N4Si4PrO4: Calculated values: C, 68.92; H, 4.98; N, 3.74. Experimental values: C, 69.11; H, 4.87; N, 3.70.

[0121] Example 5 In this example, Tb(IV) complexes and Pr(IV) complexes were prepared respectively. The specific difference from Example 1 is as follows: (1) An auxiliary ligand, 4,4'-dimethyl-2,2'-bipyridine (L4), was added. (2) The state of the anode chamber after electrolysis during the synthesis of Tb(IV) complex Tb(OSiPh3)4L4•2MeCN and Pr(IV) complex Pr(OSiPh3)4L4•2MeCN. Figure 2 Similar to Figure (c), single crystals were precipitated and the solution was red to dark red. The solution in the anode chamber was concentrated to obtain an orange-red or red solid powder product. The concentrated product and the precipitated single crystals were combined, and the yields were calculated to be 62% Pr(IV) and 90% Tb(IV), respectively.

[0122] (3) Single crystal structures show that these two compounds are isomorphic, both crystallizing in the triclinic crystal system with space group 1. P -1. The central Ln(IV) (Ln=Pr, Tb) simultaneously reacts with four Ph3SiO4 atoms. - The anionic ligand coordinates with an L4 neutral ligand in a distorted octahedral coordination environment, resulting in a neutral molecule. Two acetonitrile molecules co-crystallize. Pr(IV) ions react with Ph3SiO - The bond lengths between ligands, Pr-O, are between 2.125 and 2.136 Å, while the bond lengths between Pr(IV) ions and L4 ligands, Pr-N, are between 2.564 and 2.574 Å. The bond lengths between Tb(IV) ions and Ph₃SiO₂ are also between 2.564 and 2.574 Å. - The bond lengths between the ligands, Tb-O, range from 2.036 to 2.114 Å, and the bond lengths between the Tb(IV) ion and the L4 ligand, Tb-N, range from 2.470 to 2.478 Å. The single-crystal structure of the product obtained in this example is shown below. Figure 5 As shown.

[0123] Elemental analysis C 88 H 78 N4Si4TbO4: Calculated values: C, 69.76; H, 5.04; N, 3.78. Experimental values: C, 69.58; H, 5.17; N, 3.82.

[0124] Elemental analysis C 88 H 78N4Si4PrO4: Calculated values: C, 69.22; H, 5.15; N, 3.67. Experimental values: C, 69.33; H, 5.34; N, 3.58.

[0125] Example 6 In this example, Tb(IV) complexes and Pr(IV) complexes were prepared respectively. The specific difference from Example 1 is as follows: (1) An auxiliary ligand, 4,4'-dichloro-2,2'-bipyridine (L5), was added. (2) The state of the anode chamber after electrolysis during the synthesis of Tb(IV) complex Tb(OSiPh3)4L5•2MeCN and Pr(IV) complex Pr(OSiPh3)4L5•2MeCN. Figure 2 Similar to Figure (c), single crystals were precipitated and the solution was red to dark red. The solution in the anode chamber was concentrated to obtain an orange-red or red solid powder product. The concentrated product and the precipitated single crystals were combined, and the yields were calculated to be 59% Pr(IV) and 88% Tb(IV), respectively.

[0126] (3) Single crystal structures show that these two compounds are isomorphic, both crystallizing in the monoclinic crystal system with space group 1. P twenty one / n The central Ln(IV) (Ln = Pr, Tb) simultaneously reacts with four Ph3SiO4 atoms. - The anionic ligand coordinates with an L5 neutral ligand in a distorted octahedral coordination environment, resulting in a neutral molecule. Two acetonitrile molecules co-crystallize. Pr(IV) ions react with Ph3SiO - The bond lengths between ligands, Pr-O, range from 2.097 to 2.140 Å, while the bond lengths between Pr(IV) ions and L5 ligands, Pr-N, range from 2.566 to 2.571 Å. The bond lengths between Tb(IV) ions and Ph3SiO ions are also significant. - The bond lengths between ligands, Tb-O, range from 2.036 to 2.114 Å, and the bond lengths between Tb(IV) ions and L5 ligands, Tb-N, range from 2.470 to 2.478 Å. The specific single-crystal structure diagram is shown below. Figure 6 As shown.

[0127] Elemental analysis C 86 H 72 N4Si4Cl2TbO4: Calculated values: C, 70.05; H, 5.21; N, 3.71. Experimental values: C, 69.96; H, 5.24; N, 3.56.

[0128] Elemental analysis C 86 H 72N4Si4Cl2PrO4: Calculated values: C, 65.89; H, 4.63; N, 3.57. Experimental values: C, 65.86; H, 4.59; N, 3.53.

[0129] Example 7 In this example, Tb(IV) complexes and Pr(IV) complexes were prepared respectively. The specific difference from Example 1 is as follows: (1) An auxiliary ligand, 4,4'-dibromo-2,2'-bipyridine (L6), was added. (2) The state of the anode chamber after electrolysis during the synthesis of Tb(IV) complex Tb(OSiPh3)4L6•2MeCN and Pr(IV) complex Pr(OSiPh3)4L6•2MeCN. Figure 2 Similar to Figure (c), single crystals were precipitated and the solution was red to dark red. The solution in the anode chamber was concentrated to obtain an orange-red or red solid powder product. The concentrated product and the precipitated single crystals were combined, and the yields were calculated to be 55% Pr(IV) and 74% Tb(IV), respectively.

[0130] (3) Single crystal structures show that these two compounds are isomorphic, both crystallizing in the monoclinic crystal system with space group 1. P twenty one / n The central Ln(IV) (Ln = Pr, Tb) simultaneously reacts with four Ph3SiO4 atoms. - The anionic ligand coordinates with an L6 neutral ligand in a distorted octahedral coordination environment, resulting in a neutral molecule. Two acetonitrile molecules co-crystallize. Pr(IV) ions react with Ph3SiO - The bond lengths between ligands, Pr-O, range from 2.099 to 2.146 Å, while the bond lengths between Pr(IV) ions and L6 ligands, Pr-N, range from 2.563 to 2.574 Å. The bond lengths between Tb(IV) ions and Ph₃SiO₂... - The bond lengths between ligands, Tb-O, range from 2.045 to 2.095 Å, and the bond lengths between Tb(IV) ions and L6 ligands, Tb-N, range from 2.445 to 2.456 Å. The specific single-crystal structures are as follows: Figure 7 As shown.

[0131] Elemental analysis C 86 H 72 N4Si4Br2TbO4: Calculated values: C, 66.65; H, 4.68; N, 3.62. Experimental values: C, 66.62; H, 4.49; N, 3.59.

[0132] Elemental analysis C 86 H 72N4Si4Br2PrO4: Calculated values: C, 62.35; H, 4.38; N, 3.38. Experimental values: C, 62.17; H, 4.47; N, 3.46.

[0133] Example 8 In this example, Tb(IV) complexes and Pr(IV) complexes were prepared respectively. The specific difference from Example 1 is as follows: (1) An auxiliary ligand, 4,4'-dimethoxy-2,2'-bipyridine (L7), was added. (2) For the Pr(IV) complex Pr(OSiPh3)4L7•MeCN, the state of the anode chamber after electrolysis and Figure 2 Similar to Figure (b), no single crystals were precipitated, and the state after the electrolysis reaction was completed was a red to dark red solution; concentrating the solution in the anode chamber yielded an orange-red or red solid powder product; the calculated yield was 30% Pr(IV); For the Tb(IV) complex Tb(OSiPh3)4L7•2MeCN, the state of the anode chamber after electrolysis and Figure 2 Similar to Figure (c), single crystals precipitated, along with a red to dark red solution; the solution in the anode chamber was concentrated to obtain orange-red or red solid powder products combined with single crystals; the yield was calculated to be 66% Tb(IV).

[0134] (3) Single-crystal structures show that, apart from Pr(OSiPh3)4L7•MeCN having one acetonitrile molecule co-crystallized and Tb(OSiPh3)4L7•2MeCN having two acetonitrile molecules co-crystallized, the two compounds are highly similar. These two compounds crystallize in different space groups within the monoclinic crystal system, namely... P twenty one / n (Pr(OSiPh3)4L7•MeCN) and P 21 / c (Tb(OSiPh3)4L7•2MeCN). Two compound centers, Ln(IV) (Ln = Pr, Tb), simultaneously interact with four Ph3SiO4 compounds. - The anionic ligand coordinates with an L7 neutral ligand in a distorted octahedral coordination environment, resulting in a neutral molecule. Two acetonitrile molecules co-crystallize. Pr(IV) ions react with Ph3SiO - The bond lengths between ligands, Pr-O, range from 2.118 to 2.138 Å, while the bond lengths between Pr(IV) ions and L7 ligands, Pr-N, range from 2.538 to 2.560 Å. The bond lengths between Tb(IV) ions and Ph₃SiO₂... -The bond lengths between ligands, Tb-O, range from 2.051 to 2.083 Å, while the bond length between the Tb(IV) ion and the L7 ligand, Tb-N, is 2.154 Å. The single-crystal structure is shown below. Figure 8 As shown.

[0135] Elemental analysis C 88 H 78 N4Si4TbO6: Calculated values: C, 63.04; H, 4.43; N, 3.42. Experimental values: C, 63.07; H, 4.44; N, 3.55.

[0136] Elemental analysis C 86 H 75 N3Si4PrO6: Calculated values: C, 68.87; H, 5.04; N, 2.80. Experimental values: C, 68.87; H, 5.10; N, 2.72.

[0137] Example 9 In this example, Tb(IV) complexes and Pr(IV) complexes were prepared respectively. The specific difference from Example 1 is as follows: (1) An auxiliary ligand 4,4'-di-tert-butyl-2,2'-bipyridine (L8) was added. (2) For Pr(IV) complexes, the state of the anode chamber after electrolysis and Figure 2 Similar to Figure (b), no single crystals were precipitated, and the state after the electrolysis reaction was completed was a red to dark red solution; the solution in the anode chamber was concentrated to obtain an orange-red or red solid powder product; the chemical formulas of the Pr(IV) complexes were Pr(OSiPh3)4L8•2MeCN; the calculated yield was 30% Pr(IV). For the Tb(IV) complex Tb(OSiPh3)4L8•2MeCN, the state of the anode chamber after electrolysis and Figure 2 Similar to Figure (c), single crystals precipitated, along with a red to dark red solution; the solution in the anode chamber was concentrated to obtain orange-red or red solid powder products combined with single crystals; the yield was calculated to be 64% Tb(IV).

[0138] (3) The single crystal structure shows that Tb(OSiPh3)4L8•2MeCN crystallizes in the triclinic crystal system, with space group 4. P -1. The central Tb(IV) reacts simultaneously with four Ph3SiO4 atoms. - The anionic ligand coordinates with an L8 neutral ligand in a distorted octahedral coordination environment. Figure 11 The entire molecule is neutral, and two acetonitrile molecules co-crystallize. Tb(IV) ions react with Ph₃SiO₂. -The bond lengths between ligands, Tb-O, range from 2.038 to 2.081 Å, while the bond lengths between Tb(IV) ions and L8 ligands, Tb-N, range from 2.448 to 2.470 Å. The single-crystal structure of Tb(OSiPh3)4L8•2MeCN is shown below. Figure 9 As shown.

[0139] Elemental analysis C 94 H 90 N4Si4TbO4: Calculated values: C, 70.08; H, 5.63; N, 3.48. Experimental values: C, 69.90; H, 5.61; N, 3.48.

[0140] Elemental analysis C 94 H 90 N4Si4PrO4: Calculated values: C, 70.87; H, 5.69; N, 3.52. Experimental values: C, 70.83; H, 5.74; N, 3.52.

[0141] Example 10 In this example, Tb(IV) complexes and Pr(IV) complexes were prepared respectively. The specific difference from Example 1 is as follows: (1) An auxiliary ligand 4,4'-bis(trifluoromethyl)-2,2'-bipyridine (L9) was added; (2) For Pr(IV) complexes and Tb(IV) complexes, the state of the anode chamber after electrolysis and Figure 2 Similar to Figure (b), no single crystals were precipitated, and the state after the electrolysis reaction was completed was a red to dark red solution; the solution in the anode chamber was concentrated to obtain an orange-red or red solid powder product; the chemical formulas of the Tb(IV) complex and the Pr(IV) complex were Tb(OSiPh3)4L9•2MeCN and Pr(OSiPh3)4L9•2MeCN, respectively; the calculated yields were 37%Pr(IV) and 44%Tb(IV), respectively.

[0142] Elemental analysis C 88 H 72 N4F6Si4TbO4: Calculated value: : C, 64.65; H, 4.44; N, 3.43. Experimental values: C, 64.77; H, 4.28; N, 3.52.

[0143] Elemental analysis C 88 H 72N4F6Si4PrO4: Calculated values: C, 65.37; H, 4.49; N, 3.47. Experimental values: C, 65.32; H, 4.29; N, 3.45.

[0144] Example 11 In this example, Tb(IV) complexes and Pr(IV) complexes were prepared respectively. The specific difference from Example 1 is as follows: (1) An auxiliary ligand, methyl 2,2'-bipyridine-4,4'-dicarboxylate (L10), was added. (2) For Pr(IV) complexes and Tb(IV) complexes, the state of the anode chamber after electrolysis and Figure 2 Similar to Figure (b), no single crystals were precipitated, and the state after the electrolysis reaction was completed was a red to dark red solution; the solution in the anode chamber was concentrated to obtain an orange-red or red solid powder product; the chemical formulas of the Tb(IV) complex and the Pr(IV) complex were Tb(OSiPh3)4L10•2MeCN and Pr(OSiPh3)4L10•2MeCN, respectively; the calculated yields were 34%Pr(IV) and 39%Tb(IV), respectively.

[0145] Elemental analysis C 90 H 78 N4Si4TbO8: Calculated values: C, 66.94; H, 4.87; N, 3.47. Experimental values: C, 66.77; H, 4.79; N, 3.42.

[0146] Elemental analysis C 90 H 78 N4Si4PrO8: Calculated values: C, 67.69; H, 4.92; N, 3.51. Experimental values: C, 67.82; H, 4.87; N, 3.38.

[0147] Example 12 In this example, Tb(IV) complexes and Pr(IV) complexes were prepared respectively. The specific difference from Example 1 is as follows: (1) An auxiliary ligand, 4,4'-dinitro-2,2'-bipyridine (L11), was added. (2) For Pr(IV) complexes and Tb(IV) complexes, the state of the anode chamber after electrolysis and Figure 2Similar to Figure (b), no single crystals were precipitated, and the state after the electrolysis reaction was completed was a red to dark red solution; the solution in the anode chamber was concentrated to obtain an orange-red or red solid powder product; the chemical formulas of the Tb(IV) complex and the Pr(IV) complex were Tb(OSiPh3)4L11•MeCN and Pr(OSiPh3)4L11•MeCN, respectively; the calculated yields were 26% Pr(IV) and 34% Tb(IV), respectively.

[0148] Elemental analysis C 84 H 69 N5Si4TbO8: Calculated values: C, 65.19; H, 4.49; N, 4.52. Experimental values: C, 65.14; H, 4.62; N, 4.44.

[0149] Elemental analysis C 84 H 69 N5Si4PrO8: Calculated values: C, 65.95; H, 4.55; N, 4.58. Experimental values: C, 66.02; H, 4.60; N, 4.62.

[0150] Example 13 In this example, Tb(IV) complexes and Pr(IV) complexes were prepared respectively. The specific difference from Example 1 is as follows: (1) An additional auxiliary ligand, 1,10-phenanthroline (L12), was added. (2) For the Pr(IV) complex Pr(OSiPh3)4L12•2MeCN and the Tb(IV) complex Tb(OSiPh3)4L12•2MeCN, the state of the anode chamber after electrolysis and Figure 2 Similar to Figure (c), single crystals were precipitated and dispersed in a red to dark red solution. The solution in the anode chamber was concentrated to obtain an orange-red or red solid powder product, and the precipitated single crystals were combined. The yields were calculated to be 68% Pr(IV) and 91% Tb(IV), respectively.

[0151] (3) Single crystal structures show that these two compounds are isomorphic, both crystallizing in the monoclinic crystal system with space group 1. C 2 / c The central Ln(IV) (Ln = Pr, Tb) simultaneously reacts with four Ph3SiO4 atoms. - The anionic ligand coordinates with an L12 neutral ligand in a distorted octahedral coordination environment, resulting in a neutral molecule. Two acetonitrile molecules co-crystallize. Pr(IV) ions react with Ph3SiO -The bond lengths between ligands, Pr-O, range from 2.120 to 2.148 Å, while the bond length between Pr(IV) ions and L12 ligands, Pr-N, is 2.571 Å. The bond length between Tb(IV) ions and Ph3SiO... - The bond lengths between ligands, Tb-O, range from 2.046 to 2.098 Å, while the bond length between the Tb(IV) ion and the L12 ligand, Tb-N, is 2.468 Å. The specific single-crystal structure is shown below. Figure 10 As shown.

[0152] Elemental analysis C 88 H 74 N4Si4TbO4: Calculated values: C, 69.41; H, 4.90; N, 3.68. Experimental values: C, 69.31; H, 4.82; N, 3.54.

[0153] Elemental analysis C 88 H 74 N4Si4PrO4: Calculated values: C, 70.24; H, 4.96; N, 3.72. Experimental values: C, 70.23; H, 4.97; N, 3.76.

[0154] Example 14 In this example, Tb(IV) complexes and Pr(IV) complexes were prepared respectively. The specific difference from Example 1 is as follows: (1) An auxiliary ligand, dipyrido[3,2-a:2',3'-c]phenazine (L13), was added. (2) For Pr(IV) complexes, the state of the anode chamber after electrolysis and Figure 2 Similar to Figure (b), no single crystals were precipitated, and the state after the electrolysis reaction was completed was a red to dark red solution; the solution in the anode chamber was concentrated to obtain an orange-red or red solid powder product; the chemical formulas of the Pr(IV) complexes were Pr(OSiPh3)4L13•MeCN; the calculated yield was 39% Pr(IV). For the Tb(IV) complex Tb(OSiPh3)4L13•MeCN, the state of the anode chamber after electrolysis and Figure 2 Similar to Figure (c), single crystals precipitated, along with a red to dark red solution; the solution in the anode chamber was concentrated to obtain orange-red or red solid powder products combined with single crystals; the yield was calculated to be 88% Tb(IV).

[0155] (3) Recrystallization of Tb(OSiPh3)4L13•MeCN in THF: 50 mg of Tb(OSiPh3)4L13•MeCN was dissolved in 2 ml of THF, and then 10 ml of n-hexane was diffused into the THF solution through the liquid phase. Orange-red blocky crystals of Tb(OSiPh3)4L13 were precipitated. The crystals were found in an orthorhombic crystal system with space group _____. Pccn No solvent molecules co-crystallize.

[0156] Tb(OSiPh3)4L13•MeCN was recrystallized from toluene by dissolving 50 mg of Tb(OSiPh3)4L13•MeCN in 2 ml of toluene, followed by diffusion of 10 ml of n-hexane into the toluene solution via liquid-phase chromatography. Orange-red blocky crystals of Tb(OSiPh3)4L13•(MeCN)(Tol)2 precipitated, crystallizing in a monoclinic crystal system with space group 1. P twenty one / n One acetonitrile molecule and two toluene molecules were used as free solvents for co-crystallization. The central Tb(IV) of these compounds simultaneously reacted with four Ph3SiO4 molecules. - The anionic ligand coordinates with an L13 neutral ligand in a distorted octahedral coordination environment. Tb(IV) ions react with Ph3SiO - The bond lengths between ligands, Tb-O, range from 2.040 to 2.091 Å, and the bond lengths between Tb(IV) ions and L13 ligands, Tb-N, range from 2.468 to 2.498 Å.

[0157] Specific single crystal structures, such as Figure 11 As shown (the main single-crystal structure was not changed due to the combination of solvent molecules).

[0158] Elemental analysis C 92 H 73 N5Si4TbO4: Calculated values: C, 69.77; H, 4.65; N, 4.42. Experimental values: C, 69.89; H, 4.57; N, 4.53.

[0159] Elemental analysis C 92 H 73 N5Si4PrO4: Calculated values: C, 70.57; H, 4.70; N, 4.47. Experimental values: C, 70.55; H, 4.89; N, 4.60.

[0160] Example 15 In this example, Tb(IV) complexes and Pr(IV) complexes were prepared respectively. The specific difference from Example 1 is as follows: (1) An auxiliary ligand 1,10-o-diazaphenanthroline-5,6-dione (L14) was added. (2) For the Pr(IV) complex Pr(OSiPh3)4L14•MeCN and the Tb(IV) complex Tb(OSiPh3)4L14•MeCN, the state of the anode chamber after electrolysis and Figure 2 Similar to Figure (b), no single crystals were precipitated, and the electrolysis product was a red to dark red solution; concentrating the solution in the anode chamber yielded an orange-red or red solid powder product; the yields were 33% Pr(IV) and 32% Tb(IV), respectively.

[0161] Elemental analysis C 86 H 69 N3Si4TbO6: Calculated values: C, 68.33; H, 4.60; N, 2.78. Experimental values: C, 68.24; H, 4.55; N, 2.60.

[0162] Elemental analysis C 86 H 69 N3Si4PrO6: Calculated values: C, 69.15; H, 4.66; N, 2.81. Experimental values: C, 69.18; H, 4.62; N, 2.83.

[0163] Example 16 In this example, Tb(IV) complexes and Pr(IV) complexes were prepared respectively. The specific difference from Example 1 is as follows: (1) An auxiliary ligand 2-(quinolin-2-yl)-4,5-dihydrooxazole (L15) was added; (2) For Pr(IV) complexes, the state of the anode chamber after electrolysis and Figure 2 Similar to Figure (b), no single crystals were precipitated, and the state after the electrolysis reaction was a red to dark red solution; concentrating the solution in the anode chamber yielded an orange-red or red solid powder product; the chemical formulas of the Pr(IV) complexes were Pr(OSiPh3)4L15•3MeCN; the calculated yield was 26% Pr(IV); for the Tb(IV) complex Tb(OSiPh3)4L15•3MeCN, the state of the anode chamber after the electrolysis reaction and Figure 2 Similar to Figure (c), single crystals precipitated, along with a red to dark red solution; the solution in the anode chamber was concentrated to obtain orange-red or red solid powder products combined with single crystals; the yield was calculated to be 84% Tb(IV).

[0164] (3) The single crystal structure shows that Tb(OSiPh3)4L15•3MeCN crystallizes in the monoclinic system, with space group _____. P twenty one / cThree acetonitrile molecules co-crystallize. The central Tb(IV) molecule simultaneously reacts with four Ph3SiO molecules. - The anionic ligand coordinates with an L15 neutral ligand in a distorted octahedral coordination environment. Tb(IV) ions react with Ph3SiO - The bond lengths between ligands, Tb-O, range from 2.014 to 2.088 Å. The distance between the Tb(IV) ion and the L15 ligand varies slightly due to the different bond angles of the five-membered and six-membered rings; the bond length between N and Tb in the five-membered ring ranges from 2.395 to 2.464 Å, while the bond length between N and Tb in the six-membered ring ranges from 2.575 to 2.595 Å. The specific single-crystal structure is shown below. Figure 12 As shown.

[0165] Elemental analysis C 90 H 79 N5Si4TbO5: Calculated values: C, 68.33; H, 5.03; N, 4.43. Experimental values: C, 68.24; H, 4.85; N, 4.57.

[0166] Elemental analysis C 90 H 79 N5Si4PrO5: Calculated values: C, 69.12; H, 5.09; N, 4.48. Experimental values: C, 69.08; H, 5.03; N, 4.62.

[0167] Example 17 In this example, Tb(IV) complexes and Pr(IV) complexes were prepared respectively. The specific difference from Example 1 is as follows: (1) An auxiliary ligand, N,N-dimethylformamide (DMF), was added. (2) For the Pr(IV) complex Pr(OSiPh3)4(DMF)2 and the Tb(IV) complex Tb(OSiPh3)4(DMF)2, the state of the anode chamber after the electrolysis reaction and Figure 2 Similar to Figure (c), single crystals were precipitated in both cases, distributed in a red to dark red solution. The solution in the anode chamber was concentrated to obtain an orange-red or red solid powder product, and the precipitated single crystals were combined. The yields were calculated to be 42% Pr(IV) and 66% Tb(IV), respectively.

[0168] (3) Single crystal structures show that these two compounds are isomorphic, both crystallizing in the triclinic crystal system with space group 1. P -1. The central Ln(IV) (Ln=Pr, Tb) simultaneously reacts with four Ph3SiO4 atoms. -The anionic ligand is coordinated with two DMF molecules in a distorted octahedral coordination environment. The entire molecule is neutral and there are no solvent molecules that co-crystallize it. Pr(IV) ions react with Ph₃SiO₂. - The bond lengths between ligands, Pr-O, range from 2.094 to 2.138 Å, while the bond lengths between Pr(IV) ions and DMF ligands, Pr-O, range from 2.389 to 2.445 Å. The bond lengths between Tb(IV) ions and Ph₃SiO₂... - The bond lengths between ligands, Tb-O, range from 2.034 to 2.088 Å, while the bond lengths between Tb(IV) ions and DMF ligands, Tb-O, range from 2.290 to 2.373 Å. Specific single-crystal structures are shown below. Figure 13 As shown.

[0169] Elemental analysis C 78 H 74 N2Si4TbO6: Calculated values: C, 66.60; H, 5.30; N, 1.99. Experimental values: C, 66.76; H, 5.47; N, 1.85.

[0170] Elemental analysis C 78 H 74 N2Si4PrO6: Calculated values: C, 67.46; H, 5.37; N, 2.02. Experimental values: C, 67.64; H, 5.46; N, 2.10.

[0171] Example 18 In this example, Tb(IV) complexes and Pr(IV) complexes were prepared respectively. The specific difference from Example 1 is as follows: (1) An auxiliary ligand, N,N-diethylformamide (L16), was added. (2) For Pr(IV) complexes and Tb(IV) complexes, the state of the anode chamber after electrolysis and Figure 2 Similar to Figure (b), no single crystals were precipitated, and the electrolysis products were red to dark red solutions; concentrating the solution in the anode chamber yielded orange-red or red solid powder products; the chemical formulas of the Tb(IV) complex and the Pr(IV) complex were Tb(OSiPh3)4(L16)2 and Pr(OSiPh3)4(L16)2, respectively; the calculated yields were 18% Pr(IV) and 23% Tb(IV), respectively.

[0172] Elemental analysis C 82 H 82 N2Si4TbO6: Calculated values: C, 67.33; H, 5.65; N, 1.92. Experimental values: C, 67.47; H, 5.50; N, 1.98.

[0173] Elemental analysis C 82 H 82 N2Si4PrO6: Calculated values: C, 68.17; H, 5.72; N, 1.94. Experimental values: C, 68.05; H, 5.67; N, 1.88.

[0174] Example 19 In this example, Tb(IV) complexes and Pr(IV) complexes were prepared respectively. The specific difference from Example 1 is as follows: (1) An auxiliary ligand N,N-diisopropylformamide (L17) was added. (2) For Pr(IV) complexes and Tb(IV) complexes, the state of the anode chamber after electrolysis and Figure 2 Similar to Figure (b), no single crystals were precipitated, and the electrolysis products were red to dark red solutions. Concentrating the solution in the anode chamber yielded orange-red or red solid powder products. The chemical formulas of the Tb(IV) complex and the Pr(IV) complex were Tb(OSiPh3)4(L17)2•MeCN and Pr(OSiPh3)4(L17)2•MeCN, respectively. The calculated yields were 19% Pr(IV) and 28% Tb(IV), respectively.

[0175] Elemental analysis C 88 H 93 N3Si4TbO6: Calculated values: C, 67.75; H, 6.01; N, 2.69. Experimental values: C, 67.88; H, 5.93; N, 2.71.

[0176] Elemental analysis C 88 H 93 N3Si4PrO6: Calculated values: C, 68.55; H, 6.08; N, 2.73. Experimental values: C, 68.64; H, 6.24; N, 2.85.

[0177] Example 20 In this example, Tb(IV) complexes and Pr(IV) complexes were prepared respectively. The specific difference from Example 1 is as follows: (1) An auxiliary ligand, N-methylformamide (L18), was added. (2) For Pr(IV) complexes and Tb(IV) complexes, the state of the anode chamber after electrolysis and Figure 2Similar to Figure (b), no single crystals were precipitated, and the electrolysis products were red to dark red solutions. Concentrating the solution in the anode chamber yielded orange-red or red solid powder products. The chemical formulas of the Tb(IV) complex and the Pr(IV) complex were Tb(OSiPh3)4(L18)2•2MeCN and Pr(OSiPh3)4(L18)2•2MeCN, respectively. The calculated yields were 22%Pr(IV) and 26%Tb(IV), respectively.

[0178] Elemental analysis C 92 H 84 N4Si4TbO6: Calculated values: C, 68.51; H, 5.25; N, 3.47. Experimental values: C, 68.71; H, 5.45; N, 3.52.

[0179] Elemental analysis C 92 H 84 N4Si4PrO6: Calculated values: C, 69.28; H, 5.31; N, 3.51. Experimental values: C, 69.12; H, 5.18; N, 3.42.

[0180] Example 21 In this example, Tb(IV) complexes and Pr(IV) complexes were prepared respectively. The specific difference from Example 1 is as follows: (1) An auxiliary ligand, N-methyl-N-(2-pyridyl)carboxamide (L19), was added. (2) For Pr(IV) complexes and Tb(IV) complexes, the state of the anode chamber after electrolysis and Figure 2 Similar to Figure (b), no single crystals were precipitated, and the electrolysis products were red to dark red solutions. Concentrating the solution in the anode chamber yielded orange-red or red solid powder products. The chemical formulas of the Tb(IV) complex and the Pr(IV) complex were Tb(OSiPh3)4(L19)2•2MeCN and Pr(OSiPh3)4(L19)2•2MeCN, respectively. The calculated yields were 20% Pr(IV) and 26% Tb(IV), respectively.

[0181] Elemental analysis C 90 H 82 N6Si4TbO6: Calculated values: C, 66.94; H, 5.12; N, 5.20. Experimental values: C, 66.74; H, 5.13; N, 5.27.

[0182] Elemental analysis C 90 H 82N6Si4PrO6: Calculated values: C, 67.69; H, 5.18; N, 5.26. Experimental values: C, 67.81; H, 5.14; N, 5.42.

[0183] Example 22 In this example, Tb(IV) complexes and Pr(IV) complexes were prepared respectively. The specific difference from Example 1 is as follows: (1) An additional auxiliary ligand, N-methylimidazole (L20), was added. (2) For Pr(IV) complexes and Tb(IV) complexes, the state of the anode chamber after electrolysis and Figure 2 Similar to Figure (b), no single crystals were precipitated, and the electrolysis products were red to dark red solutions. Concentrating the solution in the anode chamber yielded orange-red or red solid powder products. The chemical formulas of the Tb(IV) complex and the Pr(IV) complex were Tb(OSiPh3)4(L20)2•MeCN and Pr(OSiPh3)4(L20)2•MeCN, respectively. The calculated yields were 9% Pr(IV) and 12% Tb(IV), respectively.

[0184] Elemental analysis C 82 H 75 N5Si4TbO4: Calculated values: C, 67.19; H, 5.16; N, 4.78. Experimental values: C, 67.03; H, 5.35; N, 4.91.

[0185] Elemental analysis C 82 H 75 N5Si4PrO4: Calculated values: C, 68.03; H, 5.22; N, 4.84. Experimental values: C, 68.16; H, 5.26; N, 5.03.

[0186] Example 23 In this example, Tb(IV) complexes and Pr(IV) complexes were prepared respectively. The specific difference from Example 1 is as follows: (1) An additional auxiliary ligand, 1-ethylimidazole (L21), was added. (2) For Pr(IV) complexes and Tb(IV) complexes, the state of the anode chamber after electrolysis and Figure 2Similar to Figure (b), no single crystals were precipitated, and the electrolysis products were red to dark red solutions. Concentrating the solution in the anode chamber yielded orange-red or red solid powder products. The chemical formulas of the Tb(IV) complex and the Pr(IV) complex are Tb(OSiPh3)4(L21)2•MeCN and Pr(OSiPh3)4(L21)2•MeCN, respectively. The calculated yields were 16% Pr(IV) and 17% Tb(IV).

[0187] Elemental analysis C 84 H 79 N5Si4TbO4: Calculated values: C, 67.54; H, 5.33; N, 4.69. Experimental values: C, 67.57; H, 5.31; N, 4.76.

[0188] Elemental analysis C 84 H 79 N5Si4PrO4: Calculated values: C, 68.36; H, 5.40; N, 4.75. Experimental values: C, 68.54; H, 5.56; N, 4.69.

[0189] Example 24 In this example, Tb(IV) complexes and Pr(IV) complexes were prepared respectively. The specific difference from Example 1 is as follows: (1) An additional auxiliary ligand, 1-propylimidazolium (L22), was added. (2) For Pr(IV) complexes and Tb(IV) complexes, the state of the anode chamber after electrolysis and Figure 2 Similar to Figure (b), no single crystals were precipitated, and the electrolysis products were red to dark red solutions; concentrating the solution in the anode chamber yielded orange-red or red solid powder products; the chemical formulas of the Tb(IV) complex and the Pr(IV) complex were Tb(OSiPh3)4(L22)2 and Pr(OSiPh3)4(L22)2, respectively; the calculated yields were 19%Pr(IV) and 19%Tb(IV), respectively.

[0190] Elemental analysis C 84 H 80 N4Si4TbO4: Calculated values: C, 68.13; H, 5.45; N, 3.78. Experimental values: C, 68.05; H, 5.37; N, 3.70.

[0191] Elemental analysis C 84 H 80N4Si4PrO4: Calculated values: C, 68.97; H, 5.51; N, 3.83. Experimental values: C, 68.88; H, 5.62; N, 3.98.

[0192] Example 25 In this example, Tb(IV) complexes and Pr(IV) complexes were prepared respectively. The specific difference from Example 1 is as follows: (1) An auxiliary ligand, trimorpholinophosphine oxide (L23), was added. (2) For Pr(IV) complexes and Tb(IV) complexes, the state of the anode chamber after electrolysis and Figure 2 Similar to Figure (b), no single crystals were precipitated, and the electrolysis products were red to dark red solutions. Concentrating the solution in the anode chamber yielded orange-red or red solid powder products. The chemical formulas of the Tb(IV) complex and the Pr(IV) complex were Tb(OSiPh3)4L23•2MeCN and Pr(OSiPh3)4L23•2MeCN, respectively. The calculated yields were 18% Pr(IV) and 19% Tb(IV), respectively.

[0193] Elemental analysis C 88 H 90 N5Si4PTbO8: Calculated values: C, 64.14; H, 5.50; N, 4.25. Experimental values: C, 63.97; H, 5.40; N, 4.15.

[0194] Elemental analysis C 88 H 90 N5Si4PPrO8: Calculated values: C, 64.85; H, 5.57; N, 4.30. Experimental values: C, 64.98; H, 5.59; N, 4.23.

[0195] Example 26 In this example, Tb(IV) complexes and Pr(IV) complexes were prepared respectively. The specific difference from Example 1 is as follows: (1) An auxiliary ligand, bis[2-[(oxo)diphenylphosphino]phenyl] ether (L24), was added. (2) For Pr(IV) complexes and Tb(IV) complexes, the state of the anode chamber after electrolysis and Figure 2Similar to Figure (b), no single crystals were precipitated, and the electrolysis products were red to dark red solutions. Concentrating the solution in the anode chamber yielded orange-red or red solid powder products. The chemical formulas of the Tb(IV) complex and the Pr(IV) complex were Tb(OSiPh3)4L24•2MeCN and Pr(OSiPh3)4L24•2MeCN, respectively. The calculated yields were 24%Pr(IV) and 27%Tb(IV), respectively.

[0196] Elemental analysis C 112 H 94 N2Si4P2TbO7: Calculated values: C, 70.31; H, 4.95; N, 1.46. Experimental values: C, 70.32; H, 5.13; N, 1.46.

[0197] Elemental analysis C 112 H 94 N2Si4P2PrO7: Calculated values: C, 70.98; H, 5.00; N, 1.48. Experimental values: C, 71.07; H, 5.10; N, 1.37.

[0198] Example 27 In this example, Tb(IV) complexes and Pr(IV) complexes were prepared respectively. The specific difference from Example 1 is as follows: (1) An auxiliary ligand, dimethyl sulfoxide (DMSO), was added; (2) For Pr(IV) complexes and Tb(IV) complexes, the state of the anode chamber after electrolysis and Figure 2 Similar to Figure (b), no single crystals were precipitated, and the electrolysis products were red to dark red solutions; concentrating the solution in the anode chamber yielded orange-red or red solid powder products; the chemical formulas of the Tb(IV) complex and the Pr(IV) complex were Tb(OSiPh3)4(DMSO)2 and Pr(OSiPh3)4(DMSO)2, respectively; the yields were 14% Pr(IV) and 16% Tb(IV), respectively.

[0199] Elemental analysis C 76 H 72 Si4S2TbO6: Calculated values: C, 64.43; H, 5.12; N, 6.78. Experimental values: C, 64.45; H, 5.27; N, 6.90.

[0200] Elemental analysis C 76 H 72Si4S2PrO6: Calculated values: C, 65.26; H, 5.19; N, 6.86. Experimental values: C, 65.09; H, 5.19; N, 6.97.

[0201] Application examples This example verifies and predicts the application prospects of the Ln(IV) complex obtained in the examples. Specifically, the product obtained in Example 4 is used as an example.

[0202] The Pr(IV) and Tb(IV) complexes obtained in Example 4 are novel paramagnetic high-valence rare-earth ligands with electronic configurations of 4f1 and 4f7, respectively, and can be used to construct single-molecule magnets with slow magnetic relaxation. Dalton Trans. 2024, 53 , 5779– 5783), qubit ( Prec. Chem. 2023, 1 (10), 583-591) or magnetic semiconductor ( Chem. Sci. 2025, 16 , 6805 – 6811).

[0203] Furthermore, the Tb(IV) complex obtained in Example 4 may also serve as a magnetic refrigerant for further cooling in cryogenic (below liquid helium) environments. Specifically, the complex Tb(OSiPh3)4L3•2MeCN at T=3.0K and The maximum magnetic entropy change occurs when H=7T. S m =6.78J Kg -1 K -1 This indicates that these novel complexes have the potential to become low-temperature magnetic refrigerants, specifically as follows: Figure 16 As shown.

[0204] Based on the same host ligand and central metal, other types of Ln(IV) complexes obtained in this invention also hold promise for further refrigeration in cryogenic environments.

[0205] In summary, this invention overcomes the bottlenecks of traditional technology through reasonable component matching, and realizes the synthesis of Ln(IV) complexes by electrochemical method. The synthesis process is simple, low-cost, easy to control, and has a high yield. The obtained products are expected to have wide applications in fields such as magnetism and optics.

[0206] The embodiments of the present invention have been described in detail above with reference to the accompanying drawings. However, the present invention is not limited to the above embodiments, and various changes can be made within the scope of knowledge possessed by those skilled in the art without departing from the spirit of the present invention. Furthermore, the embodiments of the present invention and the features thereof can be combined with each other unless otherwise specified.

Claims

1. A method for synthesizing an Ln(IV) complex, characterized in that, The synthesis method includes the following steps: Electrolytic oxidation of Ln(III) precursor in a mixed system of electron transfer medium, supporting electrolyte and solvent; The electron transfer medium includes at least one of thiaanthracene, tris(4-bromophenyl)amine, phenoxathia, and 10-methylphenothiazine; The supporting electrolyte includes at least one of tetrabutyltetrafluoroborate ammonium salt and tetrabutylhexafluorophosphate ammonium salt; The solvent includes acetonitrile; The Ln(III) precursor includes at least one of Pr(III) and Tb(III).

2. The synthesis method according to claim 1, characterized in that, The mixed system also includes auxiliary ligands, which include at least one of N-heterocyclic chelating ligands, nitrile ligands, amide ligands, imidazole ligands, phosphine oxide ligands, sulfonyl ligands, and polyacid anions.

3. The synthesis method according to claim 1, characterized in that, The mixed system also includes a host ligand, which includes a triphenylsiloxy group.

4. The synthesis method according to any one of claims 1 to 3, characterized in that, The molar ratio of the electron transfer medium to the Ln(III) precursor is 0.002 to 1:

1.

5. The synthesis method according to any one of claims 1 to 3, characterized in that, The synthesis reaction was carried out in a water-isolated environment.

6. The synthesis method according to claim 1, characterized in that, The electrochemical reaction apparatus for carrying out the synthesis method includes an anode chamber and a cathode chamber arranged with a sand core as a spacer; the Ln(III) precursor and electron transfer medium are disposed in the anode chamber; and the supporting electrolyte is disposed in the cathode chamber.

7. The synthesis method according to claim 6, characterized in that, In the cathode chamber, the concentration of the supporting electrolyte is 0.06~0.13 mol / L; and / or, in the anode chamber, the concentration of the Ln(III) precursor is 14~16 mmol / L.

8. An Ln(IV) complex, characterized in that, The chemical formula of the Ln(IV) complex is Ln(OSiPh3)4L x •aS; where Ln is Pr or Tb; x is any value between 0 and 2.5; a is any value between 0 and 3; L is the auxiliary ligand; and S is the solvent molecule.

9. The Ln(IV) complex according to claim 8, characterized in that, The space group of the Ln(IV) complex is R- 3 、P- 1 、P twenty one / n、P twenty one / c、C 2 / c、Pca 21 and Pccn One of them.

10. The application of an Ln(IV) complex as described in any one of claims 8 to 9, or an Ln(IV) complex synthesized by the synthetic method as described in any one of claims 1 to 7, in the fields of coordination chemistry, catalysis, single-molecule magnets, magnetic semiconductors, low-temperature magnetocooling, and quantum information.